O fenômeno social das “fake news” e os impactos nos direitos: a (in)efetividade da proteção jurídica dos direitos fundamentais - Souza, Igor Daniel Lima de (2021)
This research aims to deepen the understanding of the phenomenon of "fake news" and its impacts on fundamental rights. Therefore, the work addresses the historicity of lying, the concept of lying from the perspective of different theorists, the evolution of lying to the post-truth era, as this new era favored the dissemination of the phenomenon of “fake news”, the characteristics peculiar to this phenomenon, the fundamental rights violated by the dissemination of “fake news” and the mechanisms for coping with this phenomenon